NILAI AMPERE PENGELASAN SMAW DENGAN MENGGUNAKAN ELEKTRODA 6013 - Maryadi .; Rozy Hidayatullah (Institut Sains dan Teknologi Nasional, 2022)
ABSTRACT Technological developments in the increasingly advanced construction sector cannot be separated from welding. Welding has an important role in metal engineering. A good welding connection will greatly affect the welding of low, medium and high carbon materials in the SMAW (Shield Metal Arc Welding) welding process. The shipping industry in Indonesia uses a lot of 10 mm plate types, in reality welding using 10 mm plate materials is very difficult, especially in determining the number of amperes that must be used so that the welding results are said to be good. The purpose of this study was to determine a good amperage value for SMAW welding using a 10 mm A36 plate material with an E6013 electrode. By using a tensile test and a micro test by first using the experimental material in the form of a plate with type A36 which is welded using an E6013 electrode. With plate-shaped samples totaling 12 pieces using different amperes, namely 70, 110 and 160 amperes. From the results of the study it can be concluded that the best amperage and recommended for use in welding is 110 amperes. With an amperage value of this size, it will produce welding material that is not easily broken. So that in practice in the field, if this ampere value is used, it will produce a better product, more durable and have a better product selling value. Keywords: A36, E6013, Ampere, Welding.